Banned : a history of pesticides and the science of toxicology - Davis, Frederick Rowe, 1965- (Yale University Press, 2014)
This text sets Rachel Carson's study 'Silent Spring' in the context of the twentieth century, reconsiders her achievement, and analyses its legacy in light of toxic chemical use and regulation today. The book examines the history of pesticide development alongside the evolution of the science of toxicology and tracks legislation governing exposure to chemicals across the twentieth century. It affirms the brilliance of Carson's careful scientific interpretations drawing on data from university and government toxicologists.